Determinan profitabilitas pada bank pembangunan daerah di indonesia: analisis bopo, car, green banking, npl, nim, ldr dan bank size tahun 2021-2024 - Muhammad Revaldo Prasetya; Trias Madanika Kusumaningrum (Universitas Negeri Surabaya, 2026)
This study aims to analyze the determination of profitability in Regional Development Banks in Indonesia by examining operational efficiency (BOPO), capital adequacy (CAR), green banking, credit risk (NPL), net interest margin (NIM), liquidity (LDR), and bank size during the 2021-2024 period. The research uses quantitative data derived from secondary sources, including published financial statements and sustainability reports. The population of this study consists of all Regional Development Banks in Indonesia, and the sampling technique applied is saturated sampling, in which the entire population is used as the research sample. Data analysis was conducted using panel data regression with the assistance of STATA 17 software. The results reveal that BOPO has a significant negative effect on profitability, while NIM has a significant positive effect on profitability. Meanwhile, CAR, green banking, NPL, LDR, and bank size show no significant effects on profitability during the study period. These findings indicate that the ability to manage operational expenses efficiently and optimize interest income plays a crucial role in enhancing profitability. Therefore, Regional Development Banks in Indonesia should prioritize strategies focused on improving operational efficiency and strengthening intermediation performance to achieve sustainable profitability.